3-Cyanopyridine as a bridging and terminal ligand in coordination polymers. Issue 46 (14th November 2018) - Heine, Miriam; Fink, Lothar; Schmidt, Martin U.
Abstract : Crystal structures of [M II Br2 (3-CNpy) x ]( n ) with M = Mn, Fe, Co, Ni and x = 1, 2, 4 were determined by powder diffraction. For x = 1, the 3-cyanopyridine ligand is bridging two metal atoms. Abstract : 3-Cyanopyridine (3-CNpy) can act as a bridging or terminal ligand in transition metal coordination polymers. The compounds [M II Br2 (3-CNpy)4 ] with M = Mn, Fe, Co, Ni (1a–4a ) consist of individual complexes, in which the metal atom is octahedrally coordinated by two bromine atoms and four 3-cyanopyridine ligands, which coordinate through their pyridine N atoms only. Thermal decomposition at around 160 °C leads to the release of two 3-cyanopyridine molecules and the formation of [M II Br2 (3-CNpy)2 ] n with M = Mn, Fe, Co, Ni (1b–4b ). For3b and4b two polymorphs were observed each (α- 3b, β- 3b, α- 4b, β- 4b ). In all six phases the metal atoms are linked by bromine bridges into [M II Br2 ] n chains. The 3-cyanopyridine ligands again act as terminal ligands coordinating with their pyridine N atoms. Upon further heating to around 250 °C, the compounds [M II Br2 (3-CNpy)1 ] n with M = Mn, Fe, Co, Ni (1c–4c ) are obtained.1c–4c are again built up from [M II Br2 ] n chains with lateral 3-CNpy ligands, but additionally the cyano groups coordinate to the metal atoms.1c–4c are the first compounds with 3-cyanopyridine as a bridging ligand between two 3d M 2+ ions. The bridges connect neighbouring [M II Br2 ] n chains and this results in the formation of a wavy, two-dimensional network. All crystal structures were determined from X-ray powder diffraction data.